Numerical Study of Laterally Loaded Piles in Soft Clay Overlying Dense Sand - Amanpreet Kaur; Harvinder Singh; J. N. Jha (Civil Engineering Journal, 2021)
This paper presents the results of three dimensional finite element analysis of laterally loaded pile groups of configuration 1×1, 2×1 and 3×1, embedded in two-layered soil consisting of soft clay at liquid limit overlying dense sand using Plaxis 3D. Effects of variation in pile length (L) and clay layer thickness (h) on lateral capacity and bending moment profile of pile foundations were evaluated by employing different values of pile length to diameter ratio (L/D) and ratio of clay layer thickness to pile length (h/L) in the analysis. Obtained results indicated that the lateral capacity reduces non-linearly with increase in clay layer thickness. Larger decrease was observed in group piles. A non-dimensional parameter Fx ratio was defined to compare lateral capacity in layered soil to that in dense sand, for which a generalized expression was derived in terms of h/L ratio and number of piles in a group. Group effect on lateral resistance and maximum bending moment was observed to become insignificant for clay layer thickness exceeding 40% of pile length. For a fixed value of clay layer thickness, lateral capacity and bending moment in a single pile increased significantly with increase in pile length only up to an optimum embedment depth in sand layer which was found to be equal to three times pile diameter and 0.21 times pile length for pile with L/D 15. Scale effect on lateral capacity has also been studied and discussed. Doi: 10.28991/cej-2021-03091686 Full Text: PDF